CORRELATION BETWEEN INDICATORS OF MICROCIRCULATION IN CHILDREN WITH TYPE 1 DIABETES - Shevchenko , T.; Kornijko , L. (The Ukrainian Scientific Medical Youth Journal, 2017)
The study of microcirculation (MC) is of great importance. Capillaries are the first to react to the effect of various pathological factors in the body by changing the functional state and morphological rearrangement, leading to early metabolic disturbances, and with prolonged exposure to factors, are stable and often the only signs of the disease. The purpose of our work is to identify correlation relations of the microcirculatore in children with type 1 diabetes mellitus. Materials and methods. A total of 90 children with type 1 diabetes at the age of 13.59 ± 1.04 years were examined, with a duration of 4.68 ± 3.49 g. Of these, 47 were boys and 43 were girls. The vessels of the conjunctiva and the nail bed were examined. Result. Reliable correlation links between the parameters of the biomicroscopy of the conjunctiva of the eye and the nail bed have been established, which indicates the unity of the microcirculatory bed and changes in microcirculation in all parts of the blood circulation.